Self Disclosure Pengguna Bottled di Wilayah Jakarta - Evelyn Natasha; Septia Winduwati (Koneksi, 2019)
Bottled users' self-disclosure is the occurrence by writing the contents of the heart and feelings about various things as well as statements that are sometimes unable to be discussed like things that are intimately or  private when announced on general media, not anonymous. The purpose of determining how self-disclosure of anonymous social media users named Bottled. This research uses self-disclosure theory (Johari Window) and social penetration theory. This research uses a qualitative approach with the method used is a case study. Database collection technically with interviews, observation, and documentation. The key information this study were Psychologists as expert speakers and three supporting informants who were found through purposive sampling techniques.This study results reveal that self-disclosure that occurs in Bottled users makes individuals more comfortable to be open about evaluative and descriptive expressions. Bottled users' self-disclosure is also a form of self-clarification. Self disclosure pengguna Bottled ini merupakan terjadinya suatu tindakan  pengungkapan diri menggunakan menuliskan isi hati dan perasaan tentang berbagai  macam hal serta pernyataan-pernyataan yang terkadang  mampu dibicarakan misalnya hal yang bersifat intim atau terlalu privasi bila dibagikan pada media yang terlalu generik, yang bukan anonim. Penelitian ini bertujuan buat mengetahui bagaimana self-disclosure pengguna media umum anonim bernama Bottled. Penelitian ini menggunakan teori a (Johari Window) & teori penetrasi sosial. Penelitian ini memakai pendekatan kualitatif menggunakan metode yang digunakan merupakan studi perkara. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Narasumber  dalam penelitian ini adalah Psikolog menjadi narasumber pakar dan tiga informan pendukung yang ditemukan melalui teknik purposive sampling. Hasil penelitian ini mengungkapkan bahwa self disclosure yang terjadi pada pengguna Bottled berakibat individua lebih nyamana untuk terbukaa tentang ungkapan yang evaluatif & naratif. Self disclosure pengguna Bottled pula sebagai bentuk penjernihan diri.